Additional Rehabilitative Robot-Assisted Gait Training for Ambulation in Geriatric Individuals with Guillain–Barré Syndrome: A Case Report - Chen, Fred Yi-Shueh; Hou, Wen-Hsuan; Lee, Hsun-Hua; Huang, Ying-Chi; Siow, Co Yih (Medicina (Kaunas, Lithuania), 2024)
We present a case of a 75-year-old Asian woman with Guillain–Barré syndrome (GBS) who underwent a 1-month comprehensive rehabilitation training program supplemented by robot-assisted gait training (RAGT). GBS can lead to fatigue and prolonged bed rest, thereby further debilitating older patients. Although exercise intervention is recommended for GBS, a consensus regarding the appropriate intensity has yet to be established. Individualized strategies are required because older patients experience varying levels of fatigue and frailty. We used a technological adjunct to support comprehensive rehabilitation for GBS reconditioning in an older patient. To the best of our knowledge, research involving the use of an exoskeleton robotic device in the geriatric population with GBS is limited. Our case demonstrates the feasibility and safety of RAGT for improving lower limb muscle power and scores on the Barthel Index, Clinical Frailty Scale, and Instrumental Activities of Daily Living Scale at discharge from a geriatric ward.